(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study examined the interactive effect of gender and mother tongue for instruction on technical college students’ achievement and retention in blocklaying in Oyo central senatorial district technical colleges. Two research questions were raised, and were hypothesized and tested at 0.05 level of significance. Quasi-experimental research design involving a pre-test post-test non-equivalent control group design was adopted for the study. The population of the study was 461 parts 1 to 3 students offering blocklaying in the three technical colleges across the senatorial district. Sample of 83 students was drawn for the study, using purposive sampling technique. The instrument used to collect data was a Blocklaying Achievement Test (BCAT), which was validated by three experts. Kuder Richardson 20 was used to establish the reliability coefficient of 0.82 for the BCAT. For the test of hypotheses, ANCOVA was employed. Findings revealed significant interaction effects of mother tongue medium of instruction and gender on the students’ achievement and retention.